Multibeam bathymetry raw data (Atlas Hydrosweep DS echo sounder entire dataset) of RV SONNE during cruise SO96/2 - Roland von Huene; Anne-Cathrin Wölfl (PANGAEA, 2023)
Multibeam bathymetry raw data was recorded in the North Pacific during cruise SO96/2 that took place between 1994-06-28 and 1994-07-26. The data was collected using the ship extquotesingles own Atlas Hydrosweep DS echo sounder.